The Role of Digital Financial Inclusion in Improving The Sustainability of MSMEs Business after The Covid-19 Pandemic - Fitria, Ramadhani Laila; Iswanto, Dedy; Gamri, Mohammad (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
This study aims to analyze the role of digital financial inclusion in improving the sustainability of Micro, Small, and Medium Enterprises (MSMEs) post-COVID-19 pandemic through a Systematic Literature Review approach. The literature was collected from indexed databases, Google Scholar, and DOAJ, with a publication period of 2016–2025. The study results indicate that digital transformation, fintech service integration, and digital financial literacy are key pillars that support each other in promoting financial inclusion and MSME sustainability. Digital transformation improves operational efficiency and financial performance, fintech services expand access to financing and promote transparency, while digital financial literacy serves as the foundation for the effective and equitable use of financial technology. However, the study also identified significant gaps in the form of varying MSME digital readiness, limited infrastructure, low digital literacy among vulnerable communities, and regulatory uncertainty that limit optimal implementation. These findings emphasize the need for an integrative strategy that combines digitalization, financial education, and supporting policies to promote more equitable financial inclusion and MSME sustainability post-pandemic.